2016
DOI: 10.2471/blt.15.168450
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country analysis of strategies for achieving progress towards global goals for women’s and children’s health

Abstract: ObjectiveTo identify how 10 low- and middle-income countries achieved accelerated progress, ahead of comparable countries, towards meeting millennium development goals 4 and 5A to reduce child and maternal mortality.MethodsWe synthesized findings from multistakeholder dialogues and country policy reports conducted previously for the Success Factors studies in 10 countries: Bangladesh, Cambodia, China, Egypt, Ethiopia, the Lao People's Democratic Republic, Nepal, Peru, Rwanda and Viet Nam. A framework approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 11 publications
0
58
0
Order By: Relevance
“…That notwithstanding, poor use of public health facilities and poor health indicators in low resource settings persist [3]. Only 9.5% of the countries with maternal mortality ratios above 100 deaths per 100,000 live births in 1990 achieved the millennium development goal (MDG) target of three-quarter reduction in maternal mortality [4]. Of the 104 LMICs, only about 23% attained the MDG4 target to reduce under-five mortality by two-thirds relative to 1990 levels [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That notwithstanding, poor use of public health facilities and poor health indicators in low resource settings persist [3]. Only 9.5% of the countries with maternal mortality ratios above 100 deaths per 100,000 live births in 1990 achieved the millennium development goal (MDG) target of three-quarter reduction in maternal mortality [4]. Of the 104 LMICs, only about 23% attained the MDG4 target to reduce under-five mortality by two-thirds relative to 1990 levels [4].…”
Section: Introductionmentioning
confidence: 99%
“…Only 9.5% of the countries with maternal mortality ratios above 100 deaths per 100,000 live births in 1990 achieved the millennium development goal (MDG) target of three-quarter reduction in maternal mortality [4]. Of the 104 LMICs, only about 23% attained the MDG4 target to reduce under-five mortality by two-thirds relative to 1990 levels [4]. In Nigeria, despite adoption of free maternal and child healthcare policies in 2006 [5], reduction in maternal and childhood mortality rates have been lower than expected [6].…”
Section: Introductionmentioning
confidence: 99%
“…Again, when compared with uneducated women, educated women are less likely to accept that the complications of pregnancy and childbirth are inevitable acts that have been destined to happen. Studies have shown that the higher the level of education of a woman, the more chances of survival of the child and the mother during delivery 29,30 . Altogether, educated women tend to marry and to bear children later than their less educated peers; they are more likely to control their family size.…”
Section: Educational and Literacy Factorsmentioning
confidence: 99%
“…Decision makers should be aware that the SDGs and their targets are interdependent and indivisible: indicators are merely proxies to measure progress. As different regions and, more critically, nations have different sensitivities about sexual and reproductive health concerns, care must be taken to maintain a holistic perspective 42,43 . As a cautionary example, the emerging global universal health care monitoring effort takes a broad perspective in the diverse areas of reproductive, maternal, neonatal, child and adolescent health 44,45 but care should be taken for family planning, being part of clinical practice, to feature among its set of health interventions as opposed to being grouped elsewhere due to its linkages with other social conditions 46 .…”
Section: Operationalisationmentioning
confidence: 99%